Letter from Georg Bredig to Max Bredig, January 17, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) writes to his son, Max Bredig (1902-1977), about Max's bank statements and stocks.
Keywords: Third Reich; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Stocks